MICROCONTROLLER SEBAGAI PENGENDALI WAKTU PENYIRAMAN PADA TANAMAN BUAH-BUAHAN SISTEM TABULAPOT - Watiningsih, Tri; Nursuwening, Yohana; AM, Reni Sulistiyowati (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
Availability of land plants is the reason why they do not want to plant crops, especially fruits such as guava, kedondong and others, as academics eager to implement and introduce tabulapot plants that need hygienic fruits can be realized. Along with the question, it is necessary for the introduction of increased community participation in meeting the needs of their own fruits the land more hygienic through Research Lecturer Restoration "555 timer IC with Timer part of Viewer In tabulapot plants" and utilize the former cans or buckets of used as media cropping so as to implement the principles of the 3Rs. Technology is one of the breakthroughs that more and more developed by the designers of automated tools as a replacement for the operation of a manual system to an automated system, all work will work automatically with an error rate that can be as small as possible. Besides, the technology is expected to replace automated tool as an object or function of the human actors on each machine. Housing average land trying to take advantage of the narrow yard of his home for growing useful plants, including plants tabulapot, to overcome the problem of narrow land and water provision, which the working principle of a tub of water pumped into the potted plants automatically using a 555 timer IC , with automatic watering tabulapot expected to overcome the above problems from manual to automatic watering.